Prevalence and Virulence Characteristics of Enterococcus faecalis and Enterococcus faecium in Bovine Mastitis Milk Compared to Bovine Normal Raw Milk in South Korea - Hyeon-Jin Kim; Hye-Young Youn; Hye-Jeong Kang; Jin-San Moon; Yong-Seok Jang; Kwang-Young Song; Kun-Ho Seo (Animals, 2022)
Enterococcus spp. are pathogens that cause environmental mastitis and are difficult to eliminate owing to their resistance to antibiotics. To compare the virulence characteristics of isolates from bovine mastitis milk (BMM) and bovine normal raw milk (NRM), we isolated Enterococcus spp. from 39 dairy farms in South Korea from 2015–2020. A total of 122 Enterococcus spp. were identified, with Enterococcus faecalis (73.8%) accounting for the majority, followed by Enterococcus faecium (26.2%). E. faecalis isolated from BMM harbored gelE, asa1, esp, and cylA genes with a prevalence of 85.7, 71.4, 54.3, and 30.0%, respectively. These genes were significantly more abundant in BMM than in NRM, except for asa1 (p < 0.0001). Interestingly, strong biofilm and gelatinase formation was predominately observed for BMM isolates and this was significantly correlated to the presence of esp and gelE genes (p < 0.05). BMM isolates demonstrated higher resistance to tetracycline (59.3%), followed by chloramphenicol (21.0%), rifampicin (18.5%), doxycycline (4.9%), ciprofloxacin (1.2%), and nitrofurantoin (1.2%), than those from NRM. E. faecalis harboring esp, gelE, and cylA may be causative agents for bovine mastitis and act as a reservoir for the transmission of virulence factors to humans.